PENGAMATAN PERTUMBUHAN TANAMAN BAYAM (Amaranthus tricolor L.) PASCA APLIKASI BIOFERTILIZER (BAHAN AKTIF Aspergillus sp.) SEDIAAN CAIR - Yulia Astuti; Umrah; Abdul Rahim Thaha (Biocelebes, 2020)
The study about the observation of spinach (Amaranthus tricolor L.) growth after the addition of liquid biofertilizer (active ingredient Aspergillussp.) had been conducted in Taman Pangan Gizi Langaleso Village, Dolo Subdistrict, Sigi District, Central Sulawesi, and Laboratory of Biotechnology, Biology Department, Faculty of Mathematics and Natural Sciences, Tadulako University, Palu, from March to November 2018. The aim of the study was to observe the growth of spinach after the addition liquid biofertilizer (active ingredient Aspergillus sp.) along with the fermented soybean liquid waste and coconut water waste as the main media. This study was designed using the Completely Randomized Design which consisted of 7 treatments with 5 repetitions. The treatments were arranged as follows: P0 (without the addition ofbiofertilizer, as the negative control), P1 (2.5%biofertilizer addition), P2 (5%biofertilizer addition), P3 (7.5%biofertilizer addition), P4 (10%biofertilizer addition), P5 (12.5%biofertilizer addition), P6 (NPK addition, without the addition of biofertilizer, acting as the positive control). The results showed that treatment P4 was indicated as the best growth among any other treatments as well as the control, based on the parameters of the height of the plants (10 cm), the number of leaves (8.35 leaf blades), the dry weight of biomass (1.95 g), the fresh weight of canopy (4.94), the fresh weight of leaves (2.07 g), the dry weight of leaves (0.22 g), the fresh weight of roots (2.11 g), the dry weight of roots (0.24 g) and the length of the roots (12.2 cm).